Perhitungan Cadangan Premi Asuransi Jiwa dengan Metode Gross Premium Valuation (GPV) - Z, Yulia Rahmawati; Martadona, Ilham (Program Studi Aktuaria, Fakultas Sains Teknologi dan Pendidikan, Universitas Tamansiswa Padang, 2024)
Life and general insurance companies must meet the requirements for the level of financial health contained in the Financial Services Authority Regulation Number 71 of 2016, namely the level of ovability, technical reserves, investment adequacy, equity, guarantee funds, and other provisions related to financial health. The Gross Premium Valuation (GPV) method is one way of calculating premium reserves. The purpose of this study is to provide information on the mechanism for calculating life insurance premium reserves using the Gross Premium Valuation (GPV) method using the Indonesian Mortality Table IV Year 2019. From these results, it is obtained that the size of the premium reserve with the GPV method will be smaller with a larger interest rate for both female and male genders. These enlarged interest rates add to the investment income of insurance companies. This increase in investment income reduces the amount of reserves that must be prepared to pay claims that occur.